(untitled) (Journal of Economic Additions, 2026)
This study analyzes the evolution of Germany’s waste management and its transition toward a circular economy (2010–2024). Findings reveal that recycling rates rose from 62% to over 70%, while landfilling plummeted to 1%. Economically, sector revenues reached €42 billion by 2024, with circular economy revenues totaling €108 billion and the workforce expanding to 318,000 employees. Ultimately, the German model demonstrates a successful integration of environmental sustainability and economic growth, despite persistent legislative and technological challenges. Jel Classification Codes: Q01, Q53, Q56, O44, O5